Professional competence, personal occupational well-being, and mental workload of nurse educatots - A cross-sectional study in four European countries - Vauhkonen, Anneli (Elsevier, 2025)
Background: Nurse educators need a high level of professional competence to educate future health care professionals. Professional competence supports occupational well-being whilst high mental workload can undermine it. There is little existing research into nurse educators' professional competence, occupational well-being, mental workload, and the relationships between them, particularly in the European context.
Objectives: To describe the professional competence, personal occupational well-being, and mental workload of nurse educators in four European countries, and to explore how the professional competence and mental workload of nurse educators relate to their personal occupational well-being.
Design: Cross-sectional study design with quantitative survey data.
Setting: Nurse educators from Finland, Spain, Slovakia, and Malta.
Methods: The data were collected from 302 nurse educators through an online questionnaire which used the Health and Social Care Educator's Competence (HeSoEduCo) instrument. This contains 43 items which measure areas of professional competence. Statistical analysis involved descriptive and multivariate analysis.
Results: Nurse educators self-assessed their overall professional competence as high. Competence in evidence-based practice was assessed as the highest whilst cultural competence was perceived to be the lowest of the six competence areas. Nurse educators perceived their levels of personal occupational well-being and the balance of mental workload as moderate. However, these levels varied between the four countries. Professional competence, more specifically administrative and curriculum competence, and a balanced mental workload were positively related to personal occupational well-being.
Conclusions: The educators who perceive themselves to have very good professional competence and a balanced mental workload are more likely to report high occupational well-being. The findings suggest that nurse educators' cultural competence needs to be strengthened and intervention research is needed to determine ways of reducing mental workload and increasing the occupational well-being of nurse educators.